Lower tacrolimus trough levels are associated with subsequently higher acute rejection risk during the first 12 months after kidney transplantation. (3rd November 2015) - Gaynor, Jeffrey J.; Ciancio, Gaetano; Guerra, Giselle; Sageshima, Junichiro; Roth, David; Goldstein, Michael J.; Chen, Linda; Kupin, Warren; Mattiazzi, Adela; Tueros, Lissett; Flores, Sandra; Hanson, Lois; et al.
Summary: The premise that lower TAC trough levels are associated with subsequently higher first BPAR risk during the first 12 mo post‐transplant was recently questioned. Using our prospectively followed cohort of 528 adult, primary kidney transplant recipients (pooled across four randomized trials) who received reduced TAC dosing plus an IMPDH inhibitor, TAC trough levels measured at seven time points, 7, 14 days, 1, 2, 3, 6 and 9 months post‐transplant, were utilized along with Cox's model to determine the multivariable significance of TAC level( t ) (a continuous time‐dependent covariate equaling the most recently measured TAC level prior to time t ) on the hazard rate of developing first BPAR during the first 12 months post‐transplant. The percentage developing BPAR during the first 12 months post‐transplant was 10.2% (54/528). In univariable analysis, lower TAC level(t) was associated with a significantly higher BPAR rate ( P = 0.00006), and its significance was maintained even after controlling for 2 significant baseline predictors (African‐American/Hispanic Recipient and Developed DGF) in Cox's model (multivariable P = 0.0003). Use of a cutpoint, TAC level( t ) <4.0 vs. ≥4.0 ng/ml, yielded an even greater association with BPAR rate (univariable and multivariable P < 0.000001), with an estimated hazard ratio of 6.33. These results suggest that TAC levels <4.0 ng/ml should be avoided during the first 12 months post‐transplant when TAC is used in combination with fixed‐dose mycophenolate with or without corticosteroids and induction therapy.